KUALITAS PELAYANAN IZIN GANGGUAN PADA BADAN PELAYANAN PERIZINAN TERPADU KOTA PALU - Risnawati, Risnawati (Katalogis, 2016)
This research aims at finding out the service of interference license service at integrated licensing service agency palu. Types of data used are primary data and secondary data. Data collection is conducteed through observation, interviews, documentation, and triangulation technigues. Informants are chosen using purposive sampling technique. Analysis of the data is conducted using Miles dan Humberman model, namely data reduction, data presentation, and conclusion. Theory used is the theory of Zethaml Parasuraman and Berry consisting of five (5) dimensions: tangibles, reliability, responsiveness, assurance and empathy. Based on results of the research conducted, the quality of service of disturbance permit at the IntegratedLicensing Service Agency of Palu is not maximized. First: tangibles dimension namely inadequate facilities and infrastructures for example waiting room size is inadequate, chairs provided does not match the number of applicants, as well as with the number of public toilet is also inadequate. But if it is viewed in terms of apparatus appearance and neatness, it has been pretty good. Second: reliability dimension is that the ability of the apparatus using tools has been very good, but the service provided is not entirely referring to the standard operation procedures. Third; the dimension of responsiiveness is that the response of apparatus in receiving a complaint of applicants is alreadyvery good, but the speed in completing the issuance of disturbance permit is not maximized. Fourth; the assurancedimension, namely the guaratee givenby the apparatus to the applied regulation. Fifth: empathy dimension, the services provided are not discriminatoryÂ and the apparatus provide services politely and friendly. Thus, of the five dimensions of service quality above, there are things that need to be addressed, so that the quality of services provided can be maximized.